Intradural lumbar disc herniation: A case report and literature review. Issue 12 (December 2022) - Cheng, Cheng-Hsin; Che-Chao Chang, MD, PhD.; Lin, Hung-Lin; Chuang, Hao-Yu; Lin, Ruey-Mo; Foo, Ning-Ping
Abstract: Study design and objection: Intradural disc herniation is a unusual disease associated with spinal surgery. The definitive diagnosis of intradural herniation depends on intraoperative findings. Summary of background data: We present the case of a 63-year-old woman with backache and left sciatica radiation for more than two months. The L2/3 laminectomy and discectomy were performed after magnetic resonance imaging (MRI) study; however, no disc rupture was noted during surgery. Follow-up lumbar spine MRI revealed one large, ruptured disc. The patient underwent revision surgery with durotomy. The large intradural disc was found and removed piece by piece. Methods, Results, and Conclusions: Intradural disc herniation, especially large herniation, is hard to diagnose specifically despite the progression of neuroradiologic imaging techniques. A durotomy procedure should be considered if there is a missing ruptured disc or a palpable intradural mass during surgery. Abstract : Intradural disc herniation; Low back pain; Sciatica; Intervertebral disc disease; Durotomy.